(untitled) (Annals of Medical Research, 2023)
Aim: Chronification of migraine is a serious health problem with difficulties in management and is related to increased disability. Inflammation is suggested to have a role in migraine and its chronification. We aimed to determine whether systemic inflammatory response tested by serum interleukin-6 (IL-6) levels and obesity were related to migraine attack frequency. Materials and Methods: A total of 40 female participants (20 chronic migraine patients, 10 episodic migraine patients, 10 healthy controls without headache) were included in the study. None of the migraine patients were on migraine prophylaxis. Episodic migraine patients were evaluated interictally with a 72 hour headache free period before and after blood collection. Migraine headache frequency, body mass index (BMI) and age of the patients were recorded. Serum IL-6 levels were measured by ELISA method. Results: Serum IL-6 levels were significantly elevated in chronic migraine patients compared to episodic migraine patients and healthy controls. Chronic migraine patients were overweight with a BMI greater than 25 kg/m2. BMI was higher in chronic migraine patients compared to episodic migraine patients and healthy subjects even though it did not reach statistical significance. Serum IL-6 levels and BMI were positively correlated with migraine headache frequency. Conclusion: Elevated systemic circulating IL-6 levels and BMI were related to an increase in migraine headache frequency. BMI and serum IL-6 levels seem to be risk factors for chronic migraine in women. Strategies to reduce inflammation and obesity must be integrated to the treatment of chronic migraine. Identification of modifiable risk factors for chronification of migraine is crucial for sustainable treatment of migraine.